THE EFFECTIVENESS LING TIEN KUNG EXERCISE ON SELF EFFICACY AND BLOOD PRESSURE IN HYPERTENSION PATIENTS - Nindya, Anastasya; Rosaline, Mareta Dea; Tobing, Duma Lumban; Anggraeni, Diah Tika (Jurnal Ilmiah Keperawatan, 2025)
Background: Hypertension is a common chronic disease in the community that requires prevention through a healthy lifestyle and high Self Efficacy to manage it effectively. Ling Tien Kung exercise therapy, a non-pharmacological approach for hypertension, involves body movements focusing on two core exercises: empet-empet anus and jinjit-jinjit. This study aims to assess the impact of Ling Tien Kung exercise therapy on Self Efficacy and blood pressure in hypertensive patients. Methods: The research employs a pre-experimental one-group pre-post test design, with 45 respondents selected through purposive sampling. Conducted twice a week over three weeks, data were collected using the General Self Efficacy Scale (GSES) questionnaire and a blood pressure observation sheet. Results: Analysis with the Wilcoxon Signed Rank Test revealed significant improvements in Self Efficacy and reductions in blood pressure before and after the intervention (p-value = 0.000 < 0.05). Conclusion: Thus, it can be concluded that Ling Tien Kung exercise therapy positively affects Self Efficacy and blood pressure in hypertensive patients, suggesting it can be a valuable complementary therapy for managing hypertension.